Co-Creating Safety and Security? Analyzing the multifaceted field of co-creation in Finland - Raisio, Harri; Puustinen, Alisa; Valtonen, Vesa (The International Sociological Association's Research Committee on the Sociology of Disasters, 2021)
Complexity is said to be on the rise in the security environment and co-creation has been proposed as one of the ways to respond to this situation. Through co-creation, complexity is addressed by a plurality of actors and actions, instead of by any single authority or recipe. Such an approach is the main premise of the Finnish Concept for Comprehensive Security. This article seeks to answer the question of how co-creation occurs as part of societal safety and security functions in Finland and what kind of challenges and problems are involved therein. The focus of the article is on the regional and local levels of action and on the public-sector/civil-society interface. The data informing this study are 31 small-group discussions that took place in so-called security cafés. This article uses the modified ladder of safety and security co-creation derived from previous research to provide its analytical framework. The ladder of co-creation proved to be a useful analytical tool to address the phenomenon and to illustrate the multifaceted and context-dependent nature of safety and security co-creation. Results indicate that at present co-creation within the safety and security functions in Finland seems to focus more on action-oriented co-production. Citizens as volunteers participate in the functions of producing safety and security, but talk-centered, planning-oriented co-creation seems to be less common. The data also provide clear indications of the darker sides of co-creation. Co-creation may be symbolic and tokenistic in that it remains at a rhetorical level. The data also offer examples of co-contamination (the lowest level of the ladder of co-creation). These examples were related to the roles of spontaneous volunteers and emergent citizen groups.
Keywords: co-creation; safety; security; civil society; Finland; fi=Sosiaali- ja terveyshallintotiede|en=Social and Health Management|